P041 Poor Sleep and Mental Health Issues Among First Nations Peoples. (9th November 2022) - Fernandez, D; McDaid, L; Tran, N; Jabran, D; King, S; Fatima, Y
Abstract: To evaluate the evidence on sleep and mental health issues in First Nations peoples. A systematic literature search was conducted covering academic and grey literature databases for studies with quantitative data on sleep and mental health association in First Nations Peoples published until November 2021. The National Institutes of Health Quality Assessment Tool was used for quality assessment, and the Aboriginal and Torres Strait Islander Quality Appraisal Tool helped assess cultural appropriate conduct of research. Seven studies (6 cross-sectional and 1 longitudinal) among three First Nations groups (n=3075) were included. In Indigenous Australian children, arousal problems increased aggression, and withdrawn behaviour, while early bedtime protected against behavioural problems (OR: 0.48, 95% CI: 0.28 -0.82). In Native American youth, insomnia symptoms increased depressive symptoms (OR: 4.87, 95% CI: 2.4 to 9.89), while in adults, short sleep increased the risk of anxiety (16%) and affective disorders (16%). Clinical sleep issues, restless leg (OR: 1.82; 95% CI: 0.53 to 3.12), insomnia (OR: 4.49; 95% CI: 3.14 to 5.83), and apnoea (OR: 2.46; 95%CI: 0.47 to 4.46) were associated with depression. Similarly, in Ameridian/Mestizo adults, restless leg syndrome increased the risk of depression (OR: 4.5, 95% CI: 2.2 to 9.7) and anxiety (OR: 3.6, 95% CI: 1.7 to 7.7). Majority of the studies scored high in quality assessment but the lack of information limited adequately assessing cultural appropriateness. There is limited but strong evidence suggesting a strong role of poor sleep in mental health issues in First Nations peoples which compels investment in sleep health.